FEATURES OF TEACHING TERMINOLOGY OF GRAPHIC MATERIALS AND TOOLS TO THE STUDENTS OF LIGHT INDUSTRY SPECIALTIES (ON THE MATERIALS OF THE ENGLISH LANGUAGE) - Yuldasheva, Dildora (Educational Research in Universal Sciences, 2023)
This work is devoted to the peculiarities of teaching the graphic materials and tools’ terminology to future specialists of light industry. The article outlines the basic terms of graphic materials and tools necessary for drawing from life and imagination. Mastering the terminology of graphical tools by the specialists of light industry is carried out through the use of the subject texts in the English language, as well as the use of this terminology in speech.